Genotype-Specific Physiological Responses of Sugarcane to Potassium Deficiency: Integrating K Nutritional Efficiency, Photosynthesis-Related Parameters and Sugar Partitioning - Zanchim, Bruno José; Santos, Elcio Ferreira; Mateus, Nikolas Souza; Casarin, Nícolas Braga; Reis, André Rodrigues [UNESP]; Linhares, Francisco Scaglia; Lavres, José (Springer Nature, 2025)
Potassium (K) nutritional requirements for sugarcane (Saccharum spp.) is relatively high. However, genotypes differ in their K uptake efficiency (KUpE) and use efficiency (KUtE), which shapes differences in plant growth. The study aimed to gain insight into the physiological responses of two sugarcane genotypes (SP90-3414 and SP83-2847) growth under two K concentrations in the nutrient solution (low K = 1.0 mmol L−1 and adequate K = 6.0 mmol L−1). Total leaf area, root growth and photosynthesis-related parameters were not changed in SP83-2847, regardless K supply, while for SP90-3414 under low K supply, these parameters were dramatically decreased. Under either low or adequate K supply, SP83-2847 genotype has higher KUpE and KUtE (K use efficient genotype) relative to SP90-3414, showing similar shoot dry matter yield and shoot K accumulation. Moreover, SP83-2847 plants grown under low K supply showed the highest accumulation of total soluble sugar and sucrose in leaves. The enhanced K accumulation in the shoot (leaves and stem) and sugar content (soluble sugar and sucrose) in the leaves of SP83-2847 cultivar is a physiological strategy to ease K-induced deficiency stress.
Keywords: Nutrient use efficiency; Nutritional stress; Saccharumspp; Sugar accumulation; Water use efficiency